A Retrospective Nationwide Non-Interventional Study of an Aqueous Sublingual Immunotherapy Formulation Administered with a 200-µL Dosing Pump - Roger Reig, Albert; Padró Casas, Clara; Gutiérrez Fernández, Diego; Orta Cuevas, José Carlos; Sánchez López, Germán; Corzo Higueras, José Luis (Drugs - real world outcomes, 2021)
Background Convenient dosing is a key component of treatment adherence and thus efficacy and safety. Aqueous sublingual immunotherapy (SLIT) formulations can be administered with a dosing pump that delivers 200 µL of volume per actuation. Objective The objective of this study was to describe the use of Staloral ® 300 Rapid in its new dosing pump presentation and to evaluate the safety and satisfaction from both the patient and doctor. Patients and Methods We performed a retrospective non-interventional study in a population (aged 5 years or over) of individuals with allergic rhinitis or allergic asthma who were being treated with aqueous 300 index of reactivity SLIT formulations of various allergens (grass pollen, tree pollen, house dust mites). Based on a detailed, SLIT-specific, patient self-questionnaire (Quartis ® ) and the inspection of medical records, we assessed the characteristics of the SLIT, safety, patient satisfaction and willingness to continue SLIT. The physician’s satisfaction with the treatment was measured on a 0–100 visual analogue scale. Adverse events were coded with the Medical Dictionary for Regulatory Activities. Results A total of 801 valid patients were included (52.4% male; mean ± standard deviation age: 25.9 ± 17.2 years; mean time since diagnosis: 4.56 ± 4.68 years; mean time using the previous dosing pump: 19.2 ± 13.0 months; time using the 200-µL dosing pump: 14.95 ± 3.80 months). Among the study population, 317 subjects comprised the paediatric subgroup (57%: male; mean age: 9.8 ± 2.5 years). Overall, 54 patients (6.7%) reported a total of 68 adverse events (including 51 gastrointestinal adverse events). The large majority of adverse events were mild, local and transient and did not require treatment. There were no severe adverse events. The level of patient satisfaction with the ease of SLIT administration was high (84.3% overall, and 82.6% in the paediatric subgroup). The mean ± standard deviation visual analogue scale score for physician satisfaction with the treatment was 70.6 ± 25.1 out of 100. Conclusions Administration of 300 index of reactivity SLIT with a 200-µL dosing pump is safe, well tolerated and associated with good levels of patient satisfaction.